Pengaruh Bahan Ajar Berbasis Literasi Dengan Pendekatan Kontekstual Terhadap Hasil Belajar Siswa Sekolah Dasar - Ari Metalin Ika Puspita; Suciati Purwo (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The purpose of this study was to see the effect of the application of literacy based thematic teaching materials with a contextual approach to student learning outcomes. The method used in this study is a type of quantitative research. The research design used in this study was Quasi Experimental Design with the form of Nonequivalent Control Group Design. In the design of this study researchers used one experimental group with a control group that began with the pretest in each group. The results of this study found that the use of thematic teaching materials had a significant effect on student learning outcomes. Contextual based thematic teaching materials with a literacy approach can be used as supporting teaching materials in addition to the main teaching material.